Food Matters: Tasting, Teaching, Theorizing Religion and Food - Finch, Martha L. (Bulletin for the study of religion, 2017)
Each week in my religion and food course during Spring 2016, a student or I brought foods related to the religious group we were studying into the classroom for all to try. With the first dish they tasted, students asked, So what makes this food religious'? This question formed the central theme throughout the semester as we wrestled with what religion is in the context of food and foodways: the network of material aspects (food itself; practices like growing, distributing, cooking, eating; sensory experiences such as taste) and conceptual aspects (ideas, meanings, metaphors, symbols, values such as taste) of food in a particular social/cultural group. The familiar and unfamiliar foods elicited visceral reactions from students. This essay argues that paying closer attention to religion as an independent interpretive category and especially to food itself, as a material agent eliciting powerful sensory effects that precede religious ideas and enable those ideas, provides an alternative to dependence on common food studies' interpretive categories and on the Protestant-influenced focus on food as abstracted symbol or metaphor of meaning.'